STANDARD FERRIC-FERROUS POTENTIAL AND STABILITY OF FECL2+ TO 90°C. THERMODYNAMIC PROPERTIES OF FE((AQ))3+ AND FERRIC-CHLORIDE SPECIES - Tagirov B.R.; Zotov A.V.; Diakonov I.I.; Devina O.A. (My University, 2000)
Standard electrode potentials (ET0) for the reactionFe3+(aq)+0.5H2(g)=Fe2+(aq)+H+(aq)were derived from electrochemical measurements in a non-isothermal cell at temperatures from 20.8° to 90°C in HClO4 solutions with ionic strength of 0.11–1.31 m. A value of E2980=0.770±0.002 V was obtained. An equation ET0=0.6000–3.0961×10−3T+6.4351×10−4T×ln T, where T is temperature in K, based on the assumption of a constant heat capacity for the above reaction, ΔrCp0=14.84 cal/mol K [Hovey, J.K., 1988. Thermodynamics of aqueous solutions. PhD Thesis, Univ. Alberta, Edmonton, USA.], fits experimental values of ET0 from the present study together with data from Whittemore and Langmuir [Whittemore, D.O., Langmuir, D., 1972. Standard electrode potential of Fe3++e−=Fe2+ from 5–35°C. J. Chem. Eng. Data 17, 288–290.] (5°–35°C) with an uncertainty better than ±0.002 V. The standard thermodynamic properties of ferric–ferrous reaction at 25°C were calculated: ΔrG0=−17.75±0.04 kcal/mol, ΔrH0=−9.4±0.5 kcal/mol, ΔrS0=28.0±1.5 cal/mol K. Using these values and thermodynamic data for Fe(aq)2+ and H2(g) from SUPCRT92 [Johnson, J.M., Oelkers, E.H., Helgeson, H.C., 1992. SUPCRT92: a software package for calculating the standard molal thermodynamic properties of minerals, gases, aqueous species and reactions from 1 to 5000 bars and 0° to 1000°C. Computers and Geosciences 18, 899–947.], the standard thermodynamic properties for Fe(aq)3+ ion at 25°C, 1 bar were generated: ΔfG0=−4.12 kcal/mol, ΔfH0=−12.65 kcal/mol, S0=−68.9 cal/mol K. The equilibrium stability constants for the reactionFe3++Cl−=FeCl2+were generated from the comparison of ferric–ferrous electrode potentials in a non-complexing medium (HClO4) with those in HCl solutions from 25° to 90°C. A value of log β0=1.52±0.10 was obtained at 25°C, 1 bar. Experimental results were combined with the reaction enthalpies measured by Vasil'ev and Lobanov [Vasil'ev, V.P., Lobanov, G.A., 1967. Effect of temperature and ionic strength on heat of formation of hydrated FeCl2+ in aqueous solution. Russ. J. Phys. Chem. 41, 1969–1973 [in Russian].] from 10° to 55°C, to describe the temperature dependence of the stability constant, enthalpy and heat capacity for this reaction: log β10=0.018T+420.12/T−5.23; ΔrH0 (cal/mol)=−1918+0.082T2; ΔrCP0 (cal/mol K)=0.163T. This data allows calculation of the standard Gibbs energy (−37.61 kcal/mol), enthalpy (−47.21 kcal/mol), entropy (−30.2 cal/mol K) and heat capacity (−5.7 cal/mol K) for FeCl2+ using thermodynamic properties for Fe3+ and Cl− aqueous ions from this study and SUPCRT92, respectively. Thermodynamic properties of Fe3+ and FeCl2+ generated in this study together with data for FeCl2+ complex derived from the literature data (ΔfG0=−71.27 kcal/mol, ΔfH0=−81.84 kcal/mol, S0=−5.9 cal/mol K, Cp0=7.0 cal/mol K at 25°C, 1 bar) allowed calculation of hematite solubility in HCl solutions from 25° to 200°C.